High-throughput sequencing detected a virus–viroid complex in a single pokeweed plant - Kwak, Myeonghwan; Troiano, Elisa; Kil, Eui-Joon; Parrella, Giuseppe (Frontiers in Plant Science, 2024)
In this study, total RNA high-throughput sequencing (HTS) of a single symptomatic Phytolacca americana plant enabled the obtention of a nearly complete genome of two new isolates of turnip yellows virus (TuYV), named TuYV-ITA1 and TuYV-ITA2 and revealed a mixed infection with a new variant of citrus exocortis viroid (CEVd), named CEVd-ITA1. The TuYV-ITA2 isolate diverged from the known virus isolates of TuYV and showed variability in P0 and P5 readthrough domain. Recombination analysis revealed its recombinant nature between TuYV and an unidentified polerovirus. The putative recombination event was identified in the P5 readthrough domain of the TuYMV-ITA2 isolate. Our results thus represent the first report of TuYV in Italy and some molecular evidence for the possible natural co-existence of TuYV and CEVd in a new natural host for both infectious entities. This study is adding further knowledge about the role of weed plants as virus reservoirs and thus, additional biological and impact studies would be desirable to determine in particular the role of P. americana in the spread of TuYV and if this virus should be considered a new threat for the susceptible Italian crops.